2017
DOI: 10.2967/jnmt.116.180851
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance of Improved Serum Estimators of Glomerular Filtration Rate (GFR) to 99mTc-DTPA GFR Methods in Patients with Hepatic Cirrhosis

Abstract: Glomerular filtration rate (GFR) measurements are critical in patients with hepatic cirrhosis but potentially erroneous when based on serum creatinine. New equations for estimated GFR (eGFR) have shown variable performance in cirrhotics, possibly because of inaccuracies in reference methods for measured GFR (mGFR). The primary objective was to compare the performance of 4 improved eGFR equations with a 1-compartment, 2-sample plasma slope intercept 99m Tc-DTPA mGFR method to determine whether any of the eGFR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(54 reference statements)
0
5
1
Order By: Relevance
“…It is important to emphasize that the precision and accuracy reported by Kalafateli et al 8 with the CKD-EPI CystC formula (assessed only in the external validation cohort of 82 patients) was a p30 of 26.8% (95% CI: 17.8-37.1). Such figure contrasts considerably with the results from our cohort and with the majority of studies published at present [3][4][5]17,21 , in which in the cystatin C-based formulas, cystatin C is considered the biomarker with greater precision and accuracy for estimating glomerular filtration in patients with LC. Both formulas (RFH and CKD-EPI CystC) performed very similarly with respect to precision and accuracy, as well as to the underestimation of kidney function in patients with filtration > 60 ml/min/1.73m 2 and overestimation in those with filtration <60 ml/min/1.73m 2 (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that the precision and accuracy reported by Kalafateli et al 8 with the CKD-EPI CystC formula (assessed only in the external validation cohort of 82 patients) was a p30 of 26.8% (95% CI: 17.8-37.1). Such figure contrasts considerably with the results from our cohort and with the majority of studies published at present [3][4][5]17,21 , in which in the cystatin C-based formulas, cystatin C is considered the biomarker with greater precision and accuracy for estimating glomerular filtration in patients with LC. Both formulas (RFH and CKD-EPI CystC) performed very similarly with respect to precision and accuracy, as well as to the underestimation of kidney function in patients with filtration > 60 ml/min/1.73m 2 and overestimation in those with filtration <60 ml/min/1.73m 2 (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…In the MELD score, which is the international classification for organ allocation for liver transplantation, SCr has been included as an essential marker for the evaluation of transplantation, and it is the section of the score that has the most impact on mortality 1 5. Today, GFR calculated through equations based on creatinine has been shown to be inaccurate and imprecise in patients with cirrhosis, when compared with measured GFR, because the formulas are standardized in the general population 4,16,17 . In addition to presenting with factors that modify SCr concentrations, such as age, female sex, muscle mass, and nutritional status, among others, patients with LC present with high bilirubin levels that directly interfere with the diagnostic assay 15 .…”
Section: Discussionmentioning
confidence: 99%
“…All patients had pre-treatment and post-treatment serum creatinine, cystatin c, eGFR levels according to Cockcrauft-Gault, MDRD and CKD-EPI were calculated as referenced before [4,5]. Blood samples were taken at least 8 hours after fasting.…”
Section: Methodsmentioning
confidence: 99%
“…Exact calculation and determining of the glomerular filtration rate (GFR) is one of the most important criteria to calculate the dosages of chemotherapeutics in cancer patients, according to chemotherapeutics narrow blood level range. Unfortunately, we do not have satisfactory calculation methods excluding the invasive GFR calculating methods in oncology practice [4]. Direct measurement of GFR methods are the gold standards such as clearance of chromium-51 EDTA (51Cr-EDTA), inulin clearance, but these methods needs administration time, necessitate high expertise and have higher cost to use each patients in daily routine [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin-C, a protein almost entirely filtered by the kidneys, has been proposed as a more suitable marker of GFR in patients with cirrhosis. Many studies have reported better estimation of GFR with Cystatin-C-based equations [9][10][11][12][13][14][15]. However, Cystatin-C is not available in most institutions, and even in those used, its measurement is significantly more expensive than the…”
mentioning
confidence: 99%